Acoustic Surveys of the Sea Floor near Hong Kong - Chesterman, W. Deryck; St. Quinton, J. M. P.; Chan, Y.; Matthews, H. R. (The International Hydrographic Review, 2015)
An asdic survey system has been developed for mapping the pattern of sediments of the waters of the Continental Shelf near Hong Kong. A fishlike body, towed from a ship, houses a magnetostriction transmitter sending pulsed ultrasonic sound at a frequency of 48 kc/s obliquely towards the sea bed. The resulting reverberation signals from the sea bed are received by the system and presented on a chart in a map-like form as the ship traverses parallel courses over the sea bed. The fan-shaped beam faces at right angles to the ship’s course and illuminates a path 800 yards wide. The nature of the surface of the sea floor is clearly delineated, and the position of rock outcrops can be identified. “ Lloyd mirror ” interference patterns are used to determine quantitatively the slope structures in certain areas, under calm water conditions. This paper covers work carried out during 1964 by the Department of Physics at the University of Hong Kong.